Microclimate Optimization for Public Open Spaces Using Envi-Met: a Case Study of Simpang Lima Pendopo - Muhammad Fathan Akbar; Nedyomukti Imam Syafii (Sean Institute, 2025)
This study analyzes the microclimate conditions of the Simpang Lima Pendopo area and evaluates the effectiveness of three levels of design intervention—20%, 40%, and 60% optimization—in improving the thermal comfort of public open spaces. Simulations using ENVI-met were conducted at 1:00 PM, 3:00 PM, and 5:00 PM to assess air temperature, relative humidity, wind speed, and PMV values. The results indicate that the existing conditions are still influenced by the dominance of hard pavement, minimal vegetation, and limited ventilation, resulting in high thermal discomfort. The 20% intervention has limited local impact, while the 40% scenario begins to improve heat distribution and comfort in pedestrian paths. The 60% scenario proved to be the most effective with a temperature decrease of 3–4°C, stable humidity, improved micro-ventilation, and PMV reaching the “warm–comfortable” category. The combination of three layers of vegetation, reflective-permeable materials, and water elements proved to be able to reduce heat, reduce hotspots, and create even thermal comfort. These findings confirm that large-scale vegetation-based interventions and surface management are effective strategies for improving microclimate quality in tropical urban areas.